Identifying reasons of mobile phone use during assessment among university ESL learners / Noor Azli Affendy Lee and Fazrul Azmi Zulkifli - Affendy Lee, Noor Azli; Zulkifli, Fazrul Azmi (Universiti Teknologi MARA, Pulau Pinang, 2022)
Mobile phones can be very attractive to learners due to their small features. They can also allow learners to gain access to several features from anywhere and anytime. Past studies have indicated that mobile learning aids English for second language (ESL) learners more in specific language learning areas such as reading comprehension and vocabulary learning. The present study aimed to determine the level of mobile dependency among ESL students, as well as their purpose and perception of using mobile phones in a classroom reading assessment. A questionnaire was administered among 54 university students after they had completed a reading comprehension assessment. The findings indicate that most respondents use their mobile phones for translation purposes. Fortunately, the findings also show that there is low dependency on mobile phone use by the respondents. This study shows that, if used appropriately, mobile phones could serve as important tools for learning and assessment.